Prospects for the use of MIMO based on IEEE 802.11ac in IoT technologies - Sokol, G.; Podhornyi, P.; Mishenko, A.; Piskovyi, R.; Herasymov, D. (Національний університет "Полтавська політехніка ім. Юрія Кондратюка", 2020)
Over time, the requirements on the network and the level of Internet traffic become more demanding. From standard cable connection with a speed of 100 Mbps to the use of Wi-Fi at speeds up to 2.3 Gbps per channel 160 MHz (802.11ac2) with simultaneous provision of multiple input mode - multiple output with multiple users (Multi User Multiple Input Multiple Output, MU-MIMO). In addition, the introduction of 5G mobile communication systems has significantly increased the level of mobile internet traffic. The development of the next generation of 6G with speeds from 100 Gbps to 1 Tbit / s has already begun in the world when controlling the artificial intelligence network, which is planned for 2026-30. In its perspective, the expansion of the range of services based on cloud computing has given a significant impetus to the development of new areas of Internet use. As a result, various concepts based on the Internet of Things (IoT) are being rapidly implemented. As you know, this approach allows you to connect to the Internet any object equipped with sensors or sensors that can receive, transmit and process information, as well as apply different actions depending on the information received. The quality of examples can include "smart home", "smart city" and others. Implementation of communication between objects of opportunities via the Internet using Bluetooth, Wi-Fi, ZigBee, etc. Another, quite new direction is the concept of the Internet of BioNanoThings (IoBNT). As you know, a living cell is already a kind of nanomachine that is controlled by a genetic program. The cell's nucleus is the processor and memory, the mitochondria are the batteries, and the receptor proteins on the cell's surface are sensors that can receive signals, and their slit contacts with other cells can send signals. It only remains to reprogram them for your needs. At the same time, it is necessary to organize communication not only between the cells themselves, but also with the Internet. The cell can transmit bitwise information depending on the state, but at a very low speed. One of the options for implementing communications may be MIMO.

Вимоги до мережі рівень трафіку Інтернет стають все більш вибагливі. Від стандартного підключення кабелем зі швидкістю 100 Мбіт/с до використання Wi-Fi зі швидкістю до 2,3 Гбіт/с на канал 160 МГц (802.11ac2) з одночасним забезпеченням режиму множинного входу – множинного виходу з кількома користувачами (Multi User Multiple Input Multiple Output, MU-MIMO). Крім того, впровадження систем мобільного зв’язку 5G дозволило значно підвищити рівень трафіку мобільного Інтернету. В світі вже почались розробки наступного покоління 6G зі швидкостями від 100 Гбіт/с до 1 Тбіт/с при управлінні мережі штучним інтелектом, яке планують на 2026-30 рр. В свою чергу, розширення номенклатури сервісів на базі хмарних обчислень дало значний поштовх до розвитку нових напрямків застосування Інтернету. Як наслідок, швидко впроваджуються різноманітні концепції на основі Інтернету речей (Internet of Things, IoT). Як відомо, такий підхід надає можливість підключення до Інтернету будь-якого об'єкту, оснащеного датчиками або сенсорами, що можуть отримувати, передавати та обробляти інформацію, і виконувати певні дії в залежності від отриманої інформації. В якості прикладів можна вказати "розумний будинок", "розумне місто", та ін. Реалізація зв'язку між об'єктами можлива через Інтернет з використанням технологій Bluetooth, Wi-Fi, ZigBee та ін. Ще одним, досить новим напрямком є концепція Інтернету біонаноречей (Internet of BioNanoThings, IoBNT). Як відомо, жива клітина – вже є своєрідною наномашиною яка керується генетичною програмою. Процесором і пам’яттю виступає ядро клітини, мітохондрії служать батарейкою а білки-рецептори на поверхні цієї клітини – це сенсори, які можуть сприймати сигнали, а їх щілинні контакти з іншими клітинами, можуть відправляти сигнали. Залишається лише перепрограмувати їх для свої потреб. При цьому, потрібно ще організувати зв'язок не тільки між самими клітинами, але і з мережею Інтернет. Клітина може передавати побітову інформацію в залежності від стану, але з дуже низькою швидкістю. Одним з варіантів реалізації комунікацій може стати MIMO.
Перспективи застосування MIMO на основі IEEE 802.11ac в технологіях IOT
Keywords: Internet; Internet of Things; Internet of Bio-Nano things; Wi-Fi; QAM; radio frequency identification; electromagnetic communications; Інтернет; Інтернет біонано речей; Інтернет речей; Multiple Input Multiple Output